الكلمة المفردة ودلالاتها في النسق القرآني: دراسة تحليلية بلاغية (Al-Qamar, 2022)
In this study, the researcher tried to uncover some of the secrets of the Qur’anic rhetoric, by studying in the words of The Holy Qur’an, its title: “The Word “AL ḱāĮimāt ul mufrādā” and Its Indications in the Qur’anic Layout (Rhetorical and analytical study) The aim of this study is to find out the opinions of rhetorical scholars on the role of the word in the Qur’anic rhetoric, and to reveal the distinction of the Qur’anic word in its position and context, so that it is impossible for another word to perform what this word did in its context and position, through an applied study of some words of the Holy Qur’an. The researcher also mentioned that the Word indicates, in terms of its substance, form, Definition and in definition of rhetorical meanings, in the light of verses of the Holy Qur’ān and Arabic poetry. At the end of the article the researcher mentioned his findings by writing this article.
Keywords: Al-Kalimah al-Mufrada; Connotations; Quranic Style; Analytical Study